Green Synthetic Fuels: Renewable Routes for the Conversion of Non-Fossil Feedstocks into Gaseous Fuels and Their End Uses - Elena Rozzi; Francesco Demetrio Minuto; Andrea Lanzini; Pierluigi Leone (Energies, 2020)
Innovative renewable routes are potentially able to sustain the transition to a decarbonized energy economy. Green synthetic fuels, including hydrogen and natural gas, are considered viable alternatives to fossil fuels. Indeed, they play a fundamental role in those sectors that are difficult to electrify (e.g., road mobility or high-heat industrial processes), are capable of mitigating problems related to flexibility and instantaneous balance of the electric grid, are suitable for large-size and long-term storage and can be transported through the gas network. This article is an overview of the overall supply chain, including production, transport, storage and end uses. Available fuel conversion technologies use renewable energy for the catalytic conversion of non-fossil feedstocks into hydrogen and syngas. We will show how relevant technologies involve thermochemical, electrochemical and photochemical processes. The syngas quality can be improved by catalytic CO and CO2 methanation reactions for the generation of synthetic natural gas. Finally, the produced gaseous fuels could follow several pathways for transport and lead to different final uses. Therefore, storage alternatives and gas interchangeability requirements for the safe injection of green fuels in the natural gas network and fuel cells are outlined. Nevertheless, the effects of gas quality on combustion emissions and safety are considered.